Becoming a viewer again? Optimizing educational tour at IKN Nusantara to encourage community enthusiasm - Rahmawati, Rahmawati; Rohmah, Miftakhur; Ulfah, Yana; Juwita, Rina; Noor, M. Fauzan; Arifin, Zainal (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
The scenario of moving the national capital aims to equalize economic growth. In reality, the president of the Republic of Indonesia has chosen Penajam Paser Utara in East Kalimantan as the new national capital (known as IKN Nusantara). Substantively, this program is predicted to have an impact on community empowerment. To stimulate the success of capital city relocation, stakeholder participation is needed, especially local communities using a comprehensive alternative. The primary target of this paper is to channel and expose the culture of East Kalimantan via IKN Nusantara educational tourism. The mixed method approach combines quantitative techniques based on surveys and qualitative techniques through in-depth interviews. As a result, most local people in East Kalimantan are interested in taking part in the IKN Nusantara educational tour with relatively low prices and unique packaging of activities. In particular, the informants desired to be part of IKN Nusantara, including maintaining cleanliness, caring for the environment, promoting educational tours on their social accounts, and actualizing this activity as content creators. The main polemic is that even though they obtain information regarding the IKN Nusantara from various media, they are still confused about the role taken in developing the IKN Nusantara. Therefore, the government's commitment can guarantee local community access as IKN Nusantara partners. Optimism for the future agenda needs to be supported by popular and mutually-adhering policies toward holistic engagement of all stakeholders.